2011
DOI: 10.1258/ce.2011.011036
|View full text |Cite
|
Sign up to set email alerts
|

Ethicality and confidentiality: is there an inverse-care issue in general practice ethics?

Abstract: This paper discusses confidentiality as a routine issue of concern to British general practitioners participating in a qualitative study as well as in contemporaneous practice literature. While keen to reflect on routine issues, such as confidentiality, participants who professed a lack of expertise in medical ethics also perceived reluctance or inability to access educational resources or ethics support. Such lack of ability might include a perception of non-entitlement to access advice and support, a fear of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Any medical student could imagine being involved in an ethics grand round where learners were too timid to speak up on topics and share their experiences when they believed they partook in wrongdoing. Where students have a fear of censure or judgement, 24 there might be further difficulties in applying the theory that is most applicable to a problematic clinical case at hand because the relevant facts of the case might be concealed. In effect, students are prepared for the idea that doing the right thing might cost them in terms of compromised immediate goals or perhaps inconvenience on a scale running from the annoyance of colleagues to the ostracism of whistleblowers in hospital settings.…”
Section: Barriers To Translating Ethicsmentioning
confidence: 99%
“…Any medical student could imagine being involved in an ethics grand round where learners were too timid to speak up on topics and share their experiences when they believed they partook in wrongdoing. Where students have a fear of censure or judgement, 24 there might be further difficulties in applying the theory that is most applicable to a problematic clinical case at hand because the relevant facts of the case might be concealed. In effect, students are prepared for the idea that doing the right thing might cost them in terms of compromised immediate goals or perhaps inconvenience on a scale running from the annoyance of colleagues to the ostracism of whistleblowers in hospital settings.…”
Section: Barriers To Translating Ethicsmentioning
confidence: 99%
“…We reminded ourselves of the specific circumstances when confidentiality can justifiably be waived (1) with patient consent (2) to prevent significant harm to the patient or others (3) where legally mandated. The RCGP COME triggered significant debate in 2010 with their paper, ‘ Is confidentiality a con?’ which suggested that confidentiality duties for doctors are not straightforward [ 13–15 ].…”
Section: Ethical Guidelinesmentioning
confidence: 99%
“…It is a perennial concern for doctors and especially general practitioners (GPs). 1,2 The meeting was preceded by a debate conducted in the British Journal of General Practice specifically about summary care records. [3][4][5] Function creep -the idea that a tool designed for one purpose might be 'misused' for another -was a related concern.…”
Section: Policy: Concept Vs Detailmentioning
confidence: 99%